Correlation between lipoprotein(a) and parameters of fibrinolytic system in patients with deep venous thrombosis - Makarovska Bojadzieva, Tatjana; Todorovska, Elizabeta (Medical faculty, Ss Cyril and Methodius University Skopje, Macedonia, 2020)
Reduced fibrinolytic capacity in lipid metabolism disorder causes impairment of intravascular thrombogenesis resulting in a thrombotic process. Thrombogenesis imbalance is done in the wall of vascular endothelial cells. They synthesize activators and inhibitors of the fibrinolytic system, they also participate in expression and degradation of different substances, among which circulatory lipids play an important role. Dyslipidemia and impaired fibrinolysis are risk factors for thrombotic processes that include deep venous thrombosis (DVT). Having this in mind, it was our aim to examine and evaluate concentrations of fibrinolytic parameters, such as tissue plasminogen activator (t-PA), plasminogen activator inhibitor (PAI-1) and D-dimers (DD) on one hand, and on the other hand concentrations of lipid fractions, such as lipoprotein (a) - Lp(a). The principal aim of this study was to determine whether there is a correlation between three parameters of the fibrinolytic system (t-PA, PAI and D-dimers) and Lp(a). DVT was examined by applying ELISA for quantitative determination of the fibrinolytic parameters t-PA, PAI and DD and of the lipid fraction lipoprotein (a). The results obtained have shown decrease of t-PA concentration and increase of PAI-1 and DD concentrations and Lp(a) concentrations in comparison with the control group. Analysis of the results revealed several correlations between certain parameters of the fibrinolytic system and lipoprotein (a). In order to precisely define diagnosis and prophylaxis of thrombotic processes, routine application of tests for determination of fibrinolytic system parameters and lipid profile is an imperative. Thetesting of Lp(a) and fibrinolytic parameters such as t-PA, PAI-1 and DD is of great importance, especially in critical patients for early diagnosis and treatment which would significantly reduce the mortality rate of venous thromboembolism and other thrombotic disorders.
Keywords: plasminogen inhibitor-1; fibrinolysis; lipoprotein (a); tissue plasminogen activator